Aplicación de técnicas de lectura y su incidencia en el nivel de comprensión lectora, en los niños y niñas del séptimo grado del subnivel básica media de la escuela Miguel Riofrio n° 2, parroquia El Sagrario, cantón y provincia de Loja, periodo académico 2013-2014 - Torres Mocha, Fanny Irene (2014)
AND ITS IMPACT ON THE LEVEL OF READING COMPREHENSION IN CHILDREN OF SEVENTH GRADE BASIC MEDIA sublevel, MIGUEL RIOFRÍO SCHOOL No.2 THE TABERNACLE CHURCH, CANTON AND Loja province, ACADEMIC SESSION 2013 -2014. Was raised as a general objective: to contribute to the use and application of reading techniques to improve the level of reading comprehension in children of the seventh grades Sublevel Basic Media, School Miguel Riofrio No.2 Parroquia El Sagrario and Canton province of Loja, Academics 2013-2014. To know the reality in this research scenario, the Scientific Method, descriptive, analytical and hypothetical-Synthetic method was used - deductive; as the use of techniques and instruments among them this: the structured interview, questionnaire, which were vital to the collection of information. In the research work intervened 83 human talents distributed as follows: Three teachers and 80 students. After the analysis and systematization of data resulting from the field research, the following results were obtained: Teachers rarely apply techniques that affects children in their reading comprehension level, 75% of students have a level low reading comprehension due to poor implementation of reading techniques by teachers. It is concluded that the application of reading techniques they use in the process of learning teachers are not consistent and do not make use of various types of reading to improve reading comprehension of students being very important as these facilitates the development of social skills to improve communication and understanding, just as it is recommended that to achieve effective readers should create habits in our students reading strategies to 'inject' interest in wanting to read a text, teachers must have training in the use and development of methodological guidelines for reading comprehension, according to the context in which the student develops.